Activation studies of the β-carbonic anhydrases from Escherichia coli with amino acids and amines - Alessio Nocentini; Sonia Del Prete; Margaret D. Mastrolorenzo; William A. Donald; Clemente Capasso; Claudiu T. Supuran (Taylor & Francis Group, 2020)
A β-carbonic anhydrase (CA, EC 4.2.1.1) from the widespread bacterium Escherichia coli (EcoCAβ), encoded by the CynT2 gene, has been investigated for its catalytic properties and enzymatic activation by a panel of amino acids and amines. EcoCAβ showed a significant catalytic activity for the hydration of CO2 to bicarbonate and a proton, with a kinetic constant kcat of 5.3 × 105 s− and a Michaelis-Menten constant KM of 12.9 mM. The most effective EcoCAβ activators were L- and D-DOPA, L-Tyr, 4-amino-Phe, serotonin and L-adrenaline, with KAs from 2.76 to 10.7 µM. L-His, 2-pyridyl-methylamine, L-Asn and L-Gln were relatively weak activators (KAs from 36.0 to 49.5 µM). D-His, L- and D-Phe, L- and D-Trp, D-Tyr, histamine, dopamine, 2-(aminoethyl)pyridine/piperazine/morpholine, L-Asp, L- and D-Glu have KAs from 11.3 to 23.7 µM. Endogenous CA activators may play a role in bacterial virulence and colonisation of the host.